2016
DOI: 10.1128/aac.00724-16
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Mutations in Antimicrobial Resistance Loci of Pseudomonas aeruginosa Isolates from Airways of Cystic Fibrosis Patients

Abstract: bThe chronic airway infections with Pseudomonas aeruginosa in people with cystic fibrosis (CF) are treated with aerosolized antibiotics, oral fluoroquinolones, and/or intravenous combination therapy with aminoglycosides and ␤-lactam antibiotics. An international strain collection of 361 P. aeruginosa isolates from 258 CF patients seen at 30 CF clinics was examined for mutations in 17 antimicrobial susceptibility and resistance loci that had been identified as hot spots of mutation by genome sequencing of seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 66 publications
4
36
0
Order By: Relevance
“…Although loss of MexA resulted in aztreonam hypersensitivity (Table 3), observed mutations were not recurrent or spatially restricted to specific regions of the protein, making them less likely to fit the profile of gain-of-function changes. Though these results appear paradoxical, they are consistent with prior analyses of CF clinical isolates which have shown frequent missense and loss-of-function mutations in MexA (22,50). Given the correlation of MexAB-OprM overproduction with increased virulence (12), it is possible that inactivating mexA mutations reflect selection for attenuation during aztreonam therapy (51) rather than increased resistance to aztreonam itself.…”
Section: Discussionsupporting
confidence: 81%
“…Although loss of MexA resulted in aztreonam hypersensitivity (Table 3), observed mutations were not recurrent or spatially restricted to specific regions of the protein, making them less likely to fit the profile of gain-of-function changes. Though these results appear paradoxical, they are consistent with prior analyses of CF clinical isolates which have shown frequent missense and loss-of-function mutations in MexA (22,50). Given the correlation of MexAB-OprM overproduction with increased virulence (12), it is possible that inactivating mexA mutations reflect selection for attenuation during aztreonam therapy (51) rather than increased resistance to aztreonam itself.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, it was suggested that these genetic alterations could contribute to the development of a high resistance to aminoglycosides in the CF context (20,(34)(35)(36). For instance, 52 of 361 nonrelated CF isolates appeared to harbor nonsynonymous mutations in fusA1 (34). In another study, the gene was found to be mutated in 13 isolates belonging to international clone CC274, within a collection of 29 CF strains (20).…”
Section: Correlation Between Genomic Data and Resistance Phenotypesmentioning
confidence: 99%
“…A number of studies on the genomic evolution of P. aeruginosa strains in CF patients have reported that the fusA1 gene is one of the most repeatedly hit by mutations. Thus, it was suggested that these genetic alterations could contribute to the development of a high resistance to aminoglycosides in the CF context (20,(34)(35)(36). For instance, 52 of 361 nonrelated CF isolates appeared to harbor nonsynonymous mutations in fusA1 (34).…”
Section: Correlation Between Genomic Data and Resistance Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…PA (particularly mucoid strains) is the most common respiratory pathogen in CF 145 and has been associated with increased frequency of exacerbations, disease progression, and mortality in both CF 105,146,147 and non-CF bronchiec-tases. 39,40,[148][149][150][151][152] Antimicrobial resistance rates are particularly high in patients with CF 38,153,154 and MDR-PA strains may limit therapeutic options. 155 Several distinct epidemic clones of MDR-PA have disseminated globally among CF patients and centers.…”
Section: Specific Populations At Risk Cystic Fibrosis and Noncystic Fmentioning
confidence: 99%